Student Engagement ditinjau dari School Climate pada Siswa SMP Negeri 1 Labuhan Deli - Hutahaean, Theresa Yuni Kristina; Sihombing, Rosa; Matondang, Fidelia Juliati; Tarigan, Beby Astri; Mirza, Rina; Safarina, Nur Afni (Dinasti Research, 2026)
The goal of this study was to investigate the connection between student engagement and school climate at SMPNegeri 1 Labuhan Deli. This study used a quantitative approach with a sample 0f 255 students. The Sampling Disproportionate Stratified Random Sampling was the method employed. The 27-item Student Engagement measure and the 38-item School Climate scale were the two primary instruments used in this study. With the aid of SPSS Statistics 22 for Windows, the Pearson Product Moment Correlation was used to analyze the data. The analysis’s findings indicate a positive and substantial association between school climate and student engagement, with a Pearson correlation value of 0.668 and significance value (p-value) of 0.000 (p<0.05). The coefficient of determination (R2) was 0.446, indicating that school climate contributed 44.6% to student engagement, with additional factors not included in this study influencing the remaining 55.4%. These results demonstrate how crucial school climate is to raising high school students’ levels of engagement. The R Square value obtained is 0.039. This shows that the effective contribution of School Climate to Student Engagement is 3.9%, while the remaining 96.1% is influenced by factors not discussed in this study. With a pearson correlation value of r = 0.197 and a significance level of 0.002 (p < 0.05), Labuhan Deli showa a significant positive relationship between Student Engagement and School Climate. This Indicates that the level of Student Engagement increases along with the improvement in the quality of the educational environment.